2018
DOI: 10.1111/apce.12212
|View full text |Cite
|
Sign up to set email alerts
|

How Should Rural Financial Cooperatives Be Best Organized? Evidence From Ethiopia

Abstract: What is the optimal size and composition of Rural Financial Cooperatives (RFCs)? With this broad question in mind, we characterize alternative formation of RFCs and their implications in improving rural households’ access to financial services, including savings, credit and insurance services. We find that some features of RFCs have varying implications for delivering various financial services (savings, credit and insurance). We find that the size of RFCs exhibits nonlinear relationship with the various finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…The observed positive coefficient for the number of members indicated that as the number of members' increased the volume of deposits also increases, which leads to the cooperatives having more liquidity to fund their loan portfolios from which they obtain interest income for operational self-sufficiency. Our findings were not in line with the previous study that argued that large memberships make rural cooperatives financially strong by increasing their capital base [54]. Boehe and Barin Cruz [77] also noted that high membership numbers would suggest that the microfinance cooperative can generate economies of scale.…”
Section: Fixed Effects Regression Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The observed positive coefficient for the number of members indicated that as the number of members' increased the volume of deposits also increases, which leads to the cooperatives having more liquidity to fund their loan portfolios from which they obtain interest income for operational self-sufficiency. Our findings were not in line with the previous study that argued that large memberships make rural cooperatives financially strong by increasing their capital base [54]. Boehe and Barin Cruz [77] also noted that high membership numbers would suggest that the microfinance cooperative can generate economies of scale.…”
Section: Fixed Effects Regression Resultscontrasting
confidence: 99%
“…This sector has experienced fast growth in terms of the number of cooperatives, deposits mobilized, geographical areas covered, and members reached. They are the forerunners in delivering financial services for the poor that have usually been excluded by conventional financial institutions [53] and they basically rely on members' savings as a loanable fund [54]. RUSACCOs have a larger rural outreach than MFIs.…”
Section: Stylized Facts: Rural Savings and Credit Cooperatives In Ethmentioning
confidence: 99%
“…In order to optimize the loan environment for farmers, better support the development of farmers, agriculture, and rural economy, strengthen the management of small credit loans to farmers, simplify the procedures of the loan process, standardize the actual operation behavior, and achieve sustainable business development, the People's Bank of China promulgated the Interim Measures for the Management of Small Credit Loans to Farmers by Rural Credit Societies as early as 1999 and required rural credit societies to open small credit loans to farmers according to local conditions [ 1 ]. This means that, in the past, small credit loans were mainly provided by organizations or NGOs [ 2 ]. This means that lending methods that used to be implemented mainly by organizations or nongovernmental institutions can now be carried out within the framework of the financial system, and through financial innovation, the central bank hopes to improve financial services for low- and middle-income groups of farmers who have guarantee capacity and lack collateral [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…is means that, in the past, small credit loans were mainly provided by organizations or NGOs [2]. is means that lending methods that used to be implemented mainly by organizations or nongovernmental institutions can now be carried out within the framework of the financial system, and through financial innovation, the central bank hopes to improve financial services for low-and middle-income groups of farmers who have guarantee capacity and lack collateral [3].…”
Section: Introductionmentioning
confidence: 99%